SMEs Financing Issues in Malaysia: Youth Entrepreneurs Perspective - Salim, Munirah; Kassim, Salina; Mohd Thas Thaker, Mohamed Asmy (2020)
The youth unemployment rate in Malaysia is three times higher than the total population. Unemployment among youth can have negative effects on the economy and social landscape if not curbed. It is widely accepted that entrepreneurship is capable to reduce unemployment rate as well as stimulate economic growth. However, new business entry in Malaysia has stagnated in the past 10 years and remained lower than the OECD average. Access to financing is one of the most prominent challenges facing by SMEs. The situation becomes worse for youth entrepreneurs as they are considered high risk profile and unable to secure financing especially from financial institutions. A survey by Khazanah Research Institute highlighted that only 6% of youth entrepreneurs in Malaysia are getting financing from financial institutions even though financial institutions are considered as predominant source of funds to SMEs. This study aims to understand the challenges facing youth entrepreneurs in Malaysia in accessing financing from financial institutions. In line with the present aims, an attempt is made to identify sources of financing used by youth entrepreneurs, challenges encountered in accessing financing and reasons for not applying for financing. The findings are based on a sample of 260 youth entrepreneurs in Malaysia through questionnaires. The results revealed that youth entrepreneurs use informal financing sources like personal savings. The most pressing problem among youth entrepreneurs who had experiences in accessing financing assistance from financial institutions is lack of track records while interest rate is the main reason for youth entrepreneurs who never had experience in accessing financing assistance from financial institutions.